2022
DOI: 10.1093/gerona/glac234
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Is Associated With Amyloid CSF Biomarkers and Alzheimer’s Disease Diagnosis in Cognitively Impaired Patients

Abstract: Background Metabolic dysfunction and dysregulation of leptin signaling have been linked to Alzheimer’s Disease (AD)’s pathophysiology. The objectives of this study were to examine the associations between plasma leptin, cerebrospinal fluid (CSF) beta-amyloid (Aβ) and tau biomarkers (AT(N) status) and with the stage of cognitive impairment. Methods Cross-sectional analysis of data from cognitively impaired patients from a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…19 In yet another recent study of >1,000 older persons, leptin was associated with CSF Aβ (inversely), as well as with AD confirmed by CSF biomarkers, but there was no relationship to slope of cognitive decline on the Mini-Mental State Examination scores. 56 Although we did not examine for decline in cognition, we found that higher leptin and insulin levels, and lower adiponectin and RAGE levels were associated with lower levels of global cognition. Further, in additional analyses, we found relationships of insulin resistance (insulin and HOMA-IR levels) and adipokines with lower function in some (memory), but not other, cognitive domains.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…19 In yet another recent study of >1,000 older persons, leptin was associated with CSF Aβ (inversely), as well as with AD confirmed by CSF biomarkers, but there was no relationship to slope of cognitive decline on the Mini-Mental State Examination scores. 56 Although we did not examine for decline in cognition, we found that higher leptin and insulin levels, and lower adiponectin and RAGE levels were associated with lower levels of global cognition. Further, in additional analyses, we found relationships of insulin resistance (insulin and HOMA-IR levels) and adipokines with lower function in some (memory), but not other, cognitive domains.…”
Section: Discussionmentioning
confidence: 71%
“…In another recent, but much smaller, study, leptin was associated with lower MRI hippocampal volumes in those with obesity, and both leptin and the leptin‐to‐adiponectin ratio were inversely associated with cognition 19 . In yet another recent study of >1,000 older persons, leptin was associated with CSF Aβ (inversely), as well as with AD confirmed by CSF biomarkers, but there was no relationship to slope of cognitive decline on the Mini‐Mental State Examination scores 56 . Although we did not examine for decline in cognition, we found that higher leptin and insulin levels, and lower adiponectin and RAGE levels were associated with lower levels of global cognition.…”
Section: Discussionmentioning
confidence: 88%
“…We included nine prospective studies published between 2009 and 2022. All of them measured blood leptin (in serum or plasma) 57,59,85–91 . Overall, they included 5758 participants, 4033 of whom were women.…”
Section: Resultsmentioning
confidence: 99%
“…All of them measured blood leptin (in serum or plasma). 57,59,[85][86][87][88][89][90][91] Overall, they included 5758 participants, 4033 of whom were women. Their mean follow-up period was between 14.5 and 384 months, with five of them having a follow-up period inferior to 40 months.…”
Section: Leptin and Prospective Cognitive Decline: A Systematic Reviewmentioning
confidence: 99%
“…Nevertheless, the mechanistic pathway linking plasma leptin and AD-related cognitive decline is not fully understood. A recent study demonstrated a significant association between lower plasma leptin levels and decreased cerebrospinal fluid (CSF) Aβ levels . However, the study had a cross-sectional design, and there is limited information available regarding the longitudinal association between plasma leptin levels and prospective changes of brain Aβ deposition.…”
Section: Introductionmentioning
confidence: 99%